FRI0023 TREATING EARLY AND INTENSIVELY IS ASSOCIATED WITH LOWER FATIGUE LEVELS ON THE LONG TERM, EVEN IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS CONSIDERED TO HAVE A FAVOURABLE RISK PROFILE. (13th June 2020) - De Cock, D.; Nooyens, A.; Pazmino, S.; Bertrand, D.; Stouten, V.; Joly, J.; Westhovens, R.; Verschueren, P.
Abstract : Background: Fatigue is reported in up to 90% of patients with established Rheumatoid Arthritis (RA). Fatigue has a large impact on patient`s life and is perceived difficult to manage in many patients. The early disease course could constitute a window of opportunity to tackle fatigue. Objectives: To explore that, if RA can be controlled rapidly, complaints of fatigue could be less in the long run, even in patients considered at low risk to develop a severe disease course. Methods: Patients with a low risk profile recruited in the 2-year pragmatic Care in Early Rheumatoid Arthritis (CareRA) trial were used in this analysis. This low risk profile was based on the absence of erosions, rheumatoid factor, anti-citrullinated protein bodies or low disease activity status. The low-risk group was randomised to either a tight step-up starting with 15mg MTX weekly in monotherapy (MTX-TSU) or COBRA Slim, consisting of 15 mg MTX weekly and a prednisone step-down scheme starting at 30 mg. Fatigue was measured by the multi-dimensional fatigue inventory (MFI), a self-report instrument consisting of 20 questions with a Likert scale from 1-5 as answer. These 20 questions can be subdivided in five subscales (0-20) of four questions (higher scores indicating higher fatigue levels): general fatigue, mental fatigue, physical fatigue, reduced activity and reduced motivation. General fatigue means the general feeling of being tired. Mental fatigue implicates concentration and memory problems. Physical fatigue implicates a lack of energy and strength. Reduced activity means that patients can do less activities for example on one day. Reduced motivation means that patients don't want to plan or do things due to lack of motivation. MFI was obtained at baseline, at week 16, week 52 and week 104. Cobra Slim was compared with MTX-TSU by Mann-Whitney-U test. The 5 domains of the MFI of the two groups were compared by a generalized estimating equation (GEE) over 2 years adjusting for baseline MFI domain score and DAS28. Results: Of the 90 patients recruited in the low-risk group, 80 (89%) patients completed the MFI at baseline. Randomisation was successful resulting in similar baseline characteristics and MFI levels between Cobra Slim (n=38) and MTX-TSU (n=42). After 2 years of treatment, DAS28CRP levels (Slim 1.9 ±0.8 - MTX-TSU 2.2 ±1.0, p=0.253) and DAS28CRP remission (Slim 81.5% - MTX-TSU 77.1%, p=0.677) did not differ between patients. However, general (Slim 9.8 ±4.1 – MTX-TSU 13.1 ±4.0, p=0.005) and mental (Slim 6.8 ±2.7 - MTX-TSU 10.0 ±4.9, p=0.022) fatigue levels on the MFI were lower in the Cobra Slim group at week 104. GEE analysis confirmed that groups differed in the general (p=0.026) and mental (p=0.013) fatigue scale over 2 years (Figure 1 ). Conclusion: Patients treated intensively have lower fatigue levels over 2 years compared to patients treated more conservatively, even if disease activity became similar in the two groups over time. This underlines the importance of initiating an optimal intensive treatment even in so called low-risk patients. Moreover, our results show that fatigue is a heterogeneous concept, with different interactions between treatment and type of fatigue. Although our study was limited by a small sample size, the data clearly shows how to improve fatigue levels significantly in early RA. Disclosure of Interests: Diederik De Cock: None declared, Amber Nooyens: None declared, Sofia Pazmino: None declared, Delphine Bertrand: None declared, Veerle Stouten: None declared, Johan Joly: None declared, Rene Westhovens Grant/research support from: Celltrion Inc, Galapagos, Gilead, Consultant of: Celltrion Inc, Galapagos, Gilead, Speakers bureau: Celltrion Inc, Galapagos, Gilead, Patrick Verschueren Grant/research support from: Pfizer unrestricted chair of early RA research, Speakers bureau: various companies